Circulation of a Quorum-Sensing-Impaired Variant of Vibrio cholerae Strain C6706 Masks Important Phenotypes - Sandrine Stutzmann (American Society for Microbiology, 2016)
ABSTRACT Vibrio cholerae, the causative agent of cholera, is a model organism for studying virulence regulation, biofilm formation, horizontal gene transfer, and the cell-to-cell communication known as quorum sensing (QS). As in any research field, discrepancies between data from diverse laboratories are sometimes observed for V. cholerae. Such discrepancies are often caused by the use of diverse patient or environmental isolates. In this study, we investigated the inability of a few laboratories to reproduce high levels of natural transformation, a mode of horizontal gene transfer that is specifically induced on chitinous surfaces. This irreproducibility was mostly related to one specific isolate of V. cholerae: the O1 El Tor C6706 strain. C6706 was previously described as QS proficient, an important prerequisite for the induction of natural competence for transformation. To elucidate the underlying problem, we collected seven isolates of the same C6706 strain from different research laboratories in North America and Europe and compared their phenotypes. Importantly, we observed a split response with respect to QS-related gene expression, including chitin-induced natural competence and type VI secretion (T6S). While approximately half of the strains behaved as reported for several other O1 El Tor pandemic isolates that are commonly studied in the laboratory, the other half were significantly impaired in QS-related expression patterns. This impairment was caused by a mutation in a QS-related gene (luxO). We conclude that the circulation of such QS-impaired wild-type strains is responsible for masking several important phenotypes of V. cholerae, including natural competence for transformation and T6S. IMPORTANCE Phenotypic diversity between laboratory-domesticated bacterial strains is a common problem and often results in the failed reproduction of published data. However, researchers rarely compare such strains to elucidate the underlying mutation(s). In this study, we tested one of the best-studied V. cholerae isolates, O1 El Tor strain C6706 (a patient isolate from Peru), with respect to two main phenotypes: natural competence for transformation and type VI secretion. We recently demonstrated that the two phenotypes are coregulated and specifically induced upon the growth of pandemic V. cholerae O1 El Tor strains on chitinous surfaces. We provide evidence that of seven C6706 strains collected from different laboratories, four were impaired in the tested phenotypes due to a mutation in a QS gene. Collectively, our data indicate that the circulation of such a mutated wild-type strain of C6706 might have had important consequences for QS-related data.